2019
DOI: 10.1002/adfm.201904055
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile, Multicolored Photothermal Writing of Block Copolymer Structural Color

Abstract: In spite of efforts to fabricate stimuli-sensitive structural colors (SCs) of self-assembled block copolymer (BCP) photonic crystals (PCs) with potential applications in displays, media boards, and sensors, few studies have demonstrated BCP PCs suitable for high-density nonvolatile information storage. Herein, a simple but robust route for multilevel nonvolatile information recording using a BCP PC is presented. The proposed method is based on the spatially controlled crosslinking of microdomains of a BCP PC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 40 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…78 Another interesting application is colorimetric sensing. [194][195][196][197][198][199][200][201] Structural color elements can be designed such that they visually respond to different external stimuli such as temperature, chemicals, and humidity through the use of suitable materials in an optically resonant system. [202][203][204][205][206][207][208][209][210][211][212][213] The benefit of colorimetric sensing is in realizing passive devices that are untethered to an energy source.…”
mentioning
confidence: 99%
“…78 Another interesting application is colorimetric sensing. [194][195][196][197][198][199][200][201] Structural color elements can be designed such that they visually respond to different external stimuli such as temperature, chemicals, and humidity through the use of suitable materials in an optically resonant system. [202][203][204][205][206][207][208][209][210][211][212][213] The benefit of colorimetric sensing is in realizing passive devices that are untethered to an energy source.…”
mentioning
confidence: 99%
“…Recently, Kang et al found that radicals can be generated in QP2VP domains by heating, which can directly crosslink the QP2VP polymer chains. [115] By varying the amounts of quaternization and crosslinking agents used, different degrees of crosslinking were achieved across a range of temperatures. To induce crosslinking in more precise and localized areas, heating was realized via photothermal conversion using poly(3,4-ethyl-enedioxythiophene) doped with tosylate (PP-PEDOT) (Figure 7a).…”
Section: Linear Block Copolymersmentioning
confidence: 99%
“…In order to develop such a thermo‐responsive PC, we employed a PC based on a thin BCP film with self‐assembled periodic structures readily and precisely tunable upon a variety of external stimuli such as solvent, [ 25,26 ] strain, [ 27 ] electric field, [ 28 ] and photothermal energy. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%